Mobile agent approach for efficient network exploration and fault detection. (1st January 2011) - Sundari, G.; Sankaranarayanan, P.E.
Sensor nodes are tiny, inexpensive and programmable devices which combine an autonomous power supply with computing, sensing, and communication capabilities. These nodes can be deployed in an environment at a large scale to monitor the phenomena of the real world. Wireless sensor networks are an emerging field of research with many potential applications. So far, only few applications have actually been realised due to the lack of appropriate programming support. Mobile agent middleware promises to address this issue by providing higher-level programming abstractions and the ability to use agents into the network. The unique characteristics of wireless sensor networks like resource scarcity demands new algorithms for controlling agent behaviour. This paper deals with one specific behaviour called network exploration. Network exploration is needed by many applications ranging from simple data collection to network behaviour monitoring. We present a mobile agent approach on event-based programming model for fault detection using sensor networks. The goal of our work is to collect the actual sensor data rapidly from a sensor network thereby reduce time delay and improve the data packet delivery ratio.